Chinese informal sector: An exploratory study on pasar malam in Kuala Lumpur - Anonymous, - (1983)
The focus of this exploratory survey is on the functions of the Informal Sector. The writer's respondents comprise wholly of pasar malam hawkers from all around Kuala Lumpur. The data is collected through an interviewing schedule. This survey intends to find out the growth of pasar malam and also its function to the Society from its status as an informal sector. Chapter 1 deals with the importance of the study, issue of methodology, an explanation of how the survey was conducted and the problems encountered during the sur vey. Chapter 2 likewise touches upon the definitions of "Informal Sector", hawker and also a literature survey that has connections with the study at hand. Chapter 3 analyses the personal feature s and the social aspects of hawkers, their relationship with each other and also with their customers. Their attitudes and aspirations towards their work are also considered. Chapter 4 analyses the economic aspects of the hawker in Pasar malam, their income and the time of year when business is good. The way bargaining is conducted and the stabilization of prices are also noted. Chapter 5 touches on the social, economic and legal functions of pasar malm. It also deals with the differences and similarities. between pasar malam hawkers and the usual hawkers. The last chapter compares the result of this study with those obtained from other related studios. A picture of the type of pasar malam hawkers is also put forward. This chapter concludes by giving a few suggestions on why pasar malam is important to the community in Kuala Lumpur. And it is also hope that City Hall will appreciate the contributions from this sector.